Karate Kids - Sterling,Holly (London Walker Books and Subsidiaries, 2020)
Join Maya and all her friends as they get together at the dojo for their Saturday karate class! There are moves to remember, blocks to practice, and punches to perfect. Maya is a white belt, which means she$1 (Bs still a beginner, but with focus, balance, and determination $1 (Band a little help from her friends $1 (Bcan she show Sensei what she$1 (Bs got? Written and illustrated by Holly Sterling, a karate champion and teacher, this is a joyful and uplifting celebration of the sport and a must-have primer for any child hoping to be a karate kid one days
Keywords: Englisg short story book